Comparative analysis of the virulence characteristics of epidemic methicillin–resistant Staphylococcus aureus (MRSA) strains isolated from Chinese children: ST59 MRSA highly expresses core gene–encoded toxin. Issue 2 (25th May 2013) - Li, Shipeng; Sun, Jing; Zhang, Jianzhong; Li, Xiangmei; Tao, Xiaoxia; Wang, Lijuan; Sun, Mingjiao; Liu, Yingchao; Li, Juan; Qiao, Yanhong; Yu, Sangjie; Yao, Kaihu; et al.
<x xml:space="preserve">Abstract</x> This study aims to investigate the prevalence of a novel cell wall‐anchored protein gene, sasX, and to obtain information on the genetic basis for the pathogenic potential of the MRSA strains isolated from Chinese children. The molecular and virulence characteristics of the clinical strains were analyzed. Twenty‐two sequence types (STs) were obtained, with six epidemic clones ST59, ST239, ST1, ST910, ST88, and ST338 accounting for 35.8, 22, 6.6, 6.6, 5.3, and 4.1% respectively. The expression levels of hla, psmα, and RNAIII were higher in ST59 than in other STs (p < 0.05). The sasX gene was detected in 26 (10.7%) MRSA isolates. ST239‐MRSA‐SCCmecIII‐t037 (61.5%) was the predominant sasX‐positive MRSA clone. The expressions of PSMα and RNAIII were higher in sasX‐positive ST239 isolates than in sasX‐negative ST239 ones (p < 0.01). Notably, the percentage of invasive infection in infections caused by sasX‐positive ST239 MRSA was higher than that by sasX‐negative ST239 MRSA (p = 0.008). This study indicated that ST59 was the predominant clone in the MRSA isolates obtained from Chinese children and might have stronger pathogenic potential. The prevalence of the sasX gene in the MRSA isolates from children was relatively low. Furthermore, the sasX gene might be related to the expressions of PSMα and RNAIII and infection invasiveness.